Managing Education in the Global Pandemic: Best Strategy to Carry Out Natural Science Learning - Munastiwi, Erni (International Journal of Elementary Education, 2021)
The Covid-19 pandemic has had a major impact on the education sector. changing the face-to-face learning process to online requires educators to innovate to create the best strategies in learning specifically natural science subjects in elementary schools. Exploration of alternative teaching and learning models is important for optimal educational practices for students. This study aims to evaluate student learning achievement in natural science learning, analyze the impact of teaching and learning methods and material resources on student achievement, and determine the best strategy in managing natural science education practice during the Covid-19 pandemic. The survey experiment was used as the research design, occupying a 2x2 factorial design. These factors include teaching and learning methods that include online and mixed learning as well as teaching and learning material resources that include textbooks and the internet. Data collection was carried out through an online survey using google form. Data analysis was performed through t test and factorial Anova. Partly, only teaching and learning methods have a significant impact on student achievement, as indicated by the t-test result of -2.610 (p = 0.010). Teaching and learning methods and teaching and learning resources simultaneously affect student achievement of natural science lessons. The F-test obtained a value of 80,335 (p = 0.001). The combination of blended learning and teaching and learning materials sourced from the internet resulted in the achievement of a much higher score.